A Scientific Comparison of COVID-19 Vaccines: Composition, Characteristics, and Health Indicators - Al-Ahmadi, Tareq Mohammed (Journal of medical and pharmaceutical sciences, 2025)
This study was conducted to provide a comprehensive scientific and analytical comparison of six internationally recognized COVID-19 vaccines (Pfizer-BioNTech, Moderna, AstraZeneca, Sinopharm, Sputnik V, and Johnson & Johnson) based on several scientific criteria, including manufacturer, chemical composition, packaging form, country of production, concentration level, advantages, and limitations. We adopted descriptive analytical methodology with information sourced from peer-reviewed Arabic and English references. These included clinical trial results, reports from global health organizations, and studies published in reputable scientific journals. One key finding of this study was that differences in vaccine chemical composition, particularly in the type of active agent used (e.g., mRNA, viral vectors, or inactivated viruses) exert fundamental impacts on variations in efficacy, distribution, and tolerability. Vaccines based on inactivated viruses, such as Sinopharm, tend to be safer and cause fewer side effects but show lower efficacy in elderly populations. In contrast, mRNA-based vaccines, such as Pfizer and Moderna, are more effective, especially in preventing severe infection. Studies conducted in Saudi Arabia and other Arab countries indicated that public trust in the Pfizer vaccine was higher in these regions than in other countries. This study concludes with several recommendations, including the need to diversify vaccine sources and tailor different types to different age groups and local storage capacities. It also highlights a need to establish a unified national registry to monitor post-vaccination side effects, enabling systematic data analysis and evidence-based decision-making, particularly with emerging or modified vaccines. Finally, this study calls for further research into vaccine efficacy within the Arab and Gulf contexts, emphasizing the importance of collaborative research between universities and health institutions across the region to develop a robust regional database that supports informed local policymaking.